Pengaruh Layanan Informasi Menggunakan Papan Bimbingan Terhadap Pemahaman Karir Siswa Sekolah Dasar - Andriani, Miranti Widi (Universitas Nusantara PGRI Kediri, 2019)
Career understanding is interpreted as an individual effort to understand themselves both attitudes, abilities, and interests. The importance of understanding career and workplace information is a separate task for individuals. In elementary schools (ES), career understanding is a problem that is often experienced by students. This occurs when students feel unsure about what career path to choose in the future and how to formulate strategies so that their abilities and goals can be realized. Students also have not been able to determine the abilities, talents and interests that have caused confusion and certainly need guidance. The researcher considers it is necessary to implement information services using guidance boards as an effort to help students improve their career understanding. This research’s method of research is Quasi-Experimental Design which uses the equivalent time-series design. On the basis of the results of the study, it can be concluded that information services using a guidance board can affect the career understanding of elementary school students. Group analysis is done by tabulating and illustrating the pretest and posttest score charts. Visually, the results of the study indicate there is an increase in career understanding which includes self-understanding and knowledge of the workforce. Implications for further research that can be obtained is the theoretical findings in this study can be used as information in the field of guidance regarding career understanding in elementary school students, this is seen from the increasing test results.